EFL Learner Engagement in Automatic Written Evaluation - Fu, Huixia; Liu, Xiaobin (Frontiers in Psychology, 2022)
Recent years have witnessed increasing popularity in the use of automatic written evaluation (AWE) in the writing context for its immediacy and high accessibility for EFL learners. Meanwhile, the effectiveness of the AWE tool in writing accuracy and ability is fully appreciated by the previous researchers. However, students' engagement in the revising process, key factors that mediate the uptake of feedback, and learning effect have not aroused much attention as expected. Thus, this review aimed to depict a broader picture of learners' behavioral, cognitive, and affective engagement in AWE feedback to bring a further understanding of how learners process the feedback and make the decision from a psychological perspective. Firstly, widely adopted targets in AWE research are discussed. Then, the definition of learner engagement and its constructs are presented based on existing research. After that, the link between AWE feedback and learner engagement has been taken into consideration. Finally, conclusions and suggestions are provided for insightful studies.